The Shift of Staple Food from Sago to Rice: A Study about Food Security and Indigenous Communities: The Shift of Staple Food from Sago to Rice: A Study about Food Security and Indigenous Communities - Lengga Pradipta (Society, 2019)
Food security is still becoming a crucial issue in developing countries nowadays, either in urban or rural areas. There are many factors triggered this condition, such as the increase in population pressure and conflict, privatization and changing tenure arrangements, poverty, social differentiation and also environmental degradation. It’s undeniable that food security is a multidimensional problem, especially for people who lived in rural or isolated areas. In Mentawai Islands, a district located in the western part of Indonesia, the indigenous people depend on forest product (sago) as their main source of food. However, since 2012, the government has destroyed their food culture by establishing the ‘National Food Security Improvement Program’ and conducting the agricultural intensification as well as establishing 600 hectares of new rice fields in six sub - districts; South Pagai, North Pagai, Sikakap, South Sipora, North Sipora, and South Siberut. This study is conducted comprehensively using the Food Security and Vulnerability Analysis (FSVA) to understand and describe the exact profiles of food-insecurities and vulnerable households. Furthermore, it also identified the risks and vulnerabilities of food consumption in Mentawai communities. Findings depict that shifting or transforming the food culture from sago to rice is a serious issue because socio-cultural aspects influence it and surely the government has to make a parallel policy that can accommodate the people needs, not only prioritize the national development agenda.